Effects of Pinus massoniana pollen polysaccharides on intestinal microenvironment and colitis in mice. Issue 1 (9th December 2020) - Niu, Xiangyun; Shang, Hongqi; Chen, Siyan; Chen, Ruichang; Huang, Jin; Miao, Yongqiang; Cui, Wenping; Wang, Huan; Sha, Zhou; Peng, Duo; Zhu, Ruiliang
Abstract : The stability of the intestinal microenvironment is the basis for maintaining the normal physiological activities of the intestine. Abstract : The stability of the intestinal microenvironment is the basis for maintaining the normal physiological activities of the intestine. On the contrary, disordered dynamic processes lead to chronic inflammation and disease pathology. Pinus massoniana pollen polysaccharide (PPPS), isolated from Taishan Pinus massoniana pollen, has been reported with extensive biological activities, including immune regulation. However, the role of PPPS in the intestinal microenvironment and intestinal diseases is still unknown. In this work, we initiated our investigation by using 16S rRNA high-throughput sequencing technology to assess the effect of PPPS on gut microbiota in mice. The result showed that PPPS regulated the composition of gut microbiota in mice and increased the proportion of probiotics. Subsequently, we established immunosuppressive mice using cyclophosphamide (CTX) and found that PPPS regulated the immunosuppressive state of lymphocytes in Peyer's patches (PPs). Moreover, PPPS also regulated systemic immunity by acting on intestinal PPs. PPPS alleviated lipopolysaccharide (LPS) -induced Caco2 cell damage, indicating that PPPS has the ability to reduce the damage and effectively improve the barrier dysfunction in Caco2 cells. In addition, PPPS alleviated colonic injury and relieved colitis symptoms in dextran sodium sulfate (DSS)-induced colitis mice. Overall, our findings indicate that PPPS shows a practical regulatory effect in the intestinal microenvironment, which provides an essential theoretical basis for us to develop the potential application value of PPPS further.